PENGARUH BUDAYA ORGANISASI INSTALASI FARMASI TERHADAP KUALITAS PELAYANAN DALAM MENINGKATKAN KEPERCAYAAN DAN KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT SWASTA CIKAMPEK - Andi Nurzakiah Amal; Dewi Darwati Agustini; Surya Amal (Jurnal Buana Farma, 2024)
The availability of medicines, long waiting times and the attitude of staff in prescription services often cause patient dissatisfaction, so a study is needed on the factors that influence whether or not an organization is effective in achieving its goals, especially in pharmacy installations. There are four variables in this research, namely one independent variable and three dependent variables. The instrument used in the Organizational Culture variable is to measure interpersonal relationships between organizational members and understanding of organizational tasks. Service quality uses the 5Q model method, customer trust is generally conceptualized in 5 dimensions while customer satisfaction uses the SERVQUAL method. 100 employees and customers of pharmaceutical installations each became participants in this study, using the partial least squares technique to test the hypothesized relationship. The study results show that organizational culture has a positive effect on service quality (t-statistic value 5.2189 > t table 1.96), Service Quality has a positive effect on increasing Customer Trust (t-statistic value 13.2489 > t table 1.96). Service Quality has a positive effect on increasing Customer Satisfaction (t-statistic value 6.4256 > t table 1.96) and Customer Trust has a positive effect on Customer Satisfaction (t-statistic value 4.1696 > t table 1.96). The results of this research show that the performance of services provided by private hospitals in Cikampek can generally meet patient expectations in terms of quality of service processes, quality of objects, infrastructure, interactions and atmosphere.